'Black and white and every wrong colour': The medical history of Jane Austen and the possibility of systemic lupus erythematosus. (April 2021) - Sanders, Michael D; Graham, Elizabeth M
Jane Austen died 200 years ago at the age of 41 and authors have attributed her premature death to a wide variety of causes, which include Addison's disease and lymphoma. We have reviewed all of her available letters and extricated relevant medical information which reveal rheumatism, facial skin lesions, fever and marked fluctuation of these symptoms. The severity of these symptoms increased, leading to her death within a year. This range of clinical features fulfils the most recent classification criteria for systemic lupus erythematosus.